H.E.S.S. Observations of Extragalactic Jet Sources - Böttcher, Markus (2015)
The High Energy Stereoscopic System (H.E.S.S.) is the world’s largest currently operating Atmospheric Cherenkov Telescope Array. This paper presents highlights of recent results from H.E.S.S. observations of extragalactic jet sources. It will focus on variability studies of the wellknown blazars Mrk 501 (discovering minute-scale variability at energies > 2 TeV) and PKS 2155-304, the multiwavelength analysis of the recently discovered blazar PKS 1440-389, and observations of the gravitationally lensed blazar PKS 1830-211, including a brief discussion of the implications of its non-detection by H.E.S.S.